Examples

Example 1
You are here

Example 2 Important

Example 3 Important

Example 4

Question 1 Important Deleted for CBSE Board 2025 Exams

Question 2 Important Deleted for CBSE Board 2025 Exams

Question 3 Deleted for CBSE Board 2025 Exams

Question 4 Important Deleted for CBSE Board 2025 Exams

Question 5 Deleted for CBSE Board 2025 Exams

Question 6 Important Deleted for CBSE Board 2025 Exams

Question 7 Important Deleted for CBSE Board 2025 Exams

Question 8 Deleted for CBSE Board 2025 Exams

Question 9 Important Deleted for CBSE Board 2025 Exams

Question 10 Important Deleted for CBSE Board 2025 Exams

Question 11 Important Deleted for CBSE Board 2025 Exams

Question 12 Deleted for CBSE Board 2025 Exams

Question 13 Important Deleted for CBSE Board 2025 Exams

Chapter 7 Class 11 Binomial Theorem

Serial order wise

Last updated at April 16, 2024 by Teachoo

Example 1 Expand ("x2 + " 3/x)^4 , x ≠ 0 We know that (a + b)n = nC0 an + nC1 an – 1 b1 + nC2 an – 2 b2 + ….…. + nCn – 1 a1 bn – 1 + nCn bn Hence, (a + b)4 = 4C0 a4 + 4C1 a3 b1 + 4C2 a2 b2 + 4C3 a1b3 + 4C4 b4 = 4!/0!( 4 − 0)! a4 + 4!/(1! (4 − 1)!) a2 b2 + 4!/2!(4 − 2)! ab3 + 4!/(4!(4 − 4)!) b4 = 4!/(1 × 4!) a4 + 4!/(1 × 3!) a3 b + 4!/(2 × 2!) a2 b2 + 4!/(6 × 1!) ab3 + 4!/(4! × 0!) b4 = a4 + 4a3 b + 6a2 b2 + 4 ab3 + b4 Hence, (a + b)4 = a4 + 4a3 b + 6a2 b2 + 4 ab3 + b4 Putting a = x2 and b = 𝟑/𝒙 ("x2 + " 3/x)^4 = (𝑥^2 )^4 + 4 (𝑥^2 )^3 (3/x) + 6(𝑥^2 )^2 (3/x)^2 + 4 (𝑥^2 ) (3/x)^3+ (3/x)^4 = 𝑥8 + 4x6 . 3/𝑥 + 6𝑥4 . 9/𝑥2 + 4 𝑥2 . 27/𝑥3 + 81/𝑥4 = 𝑥8 + 12 𝑥6/𝑥 + 54 . 𝑥4/𝑥2 + 108 . 𝑥2/𝑥3 + 81/𝑥4 = 𝒙𝟖 + 12 𝒙5 + 54 𝒙2 + 𝟏𝟎𝟖/𝒙 + 𝟖𝟏/𝒙𝟒